ANALYSIS OF SEAWEED CULTIVATION DEVELOPMENT STRATEGIES IN MUARA PAGATAN VILLAGE SUB-DISTRICT KUSAN HILIR DISTRICT TANAH BUMBU - Al Mughni, Muhammad Johari; Rifa’i, Muhammad Ahsin; Tony, Frans; Syahdan, Muhammad (EnviroScienteae, 2024)
Seaweed is a food commodity with benefits in the food industry, pharmaceuticals and others. Muara Pagatan Village is located in Kusan Hilir District, Tanah Bumbu Regency. According to Mughni (2021), Muara Pagatan Village has 12 households with seaweed cultivation. Based on that, it is necessary to study the development strategy of seaweed cultivation in Muara Pagatan Village. The approach used in the acquisition of seaweed aquaculture development strategies is the SWOT approach (strengths, weaknesses, opportunities and threats) and a participatory approach involving stakeholders, government and the community of Muara Pagatan Village, this research uses questionnaires distributed to representatives of RTP Muara Pagatan Village. The results of this study include 4 SWOT parameters which include, strengths in the form of land feasibility/potential, growth rate, accessibility and quality of seeds, for weaknesses in the form of limited capital, less innovative and not optimal production results. Meanwhile, opportunities include high demand, cooperation with other parties, government assistance, lack of competitors and availability of labor, for threat parameters include industrial activities, pests and diseases, weather, abrasion and prices. After that, SWOT analysis was carried out in obtaining seaweed cultivation development strategies, there were 9 priority strategies obtained based on SWOT parameters.